Pre-emptive morphine during therapeutic hypothermia after neonatal encephalopathy: a secondary analysis - Thayyil,S; Liow,N; Montaldo,P; Lally,P; Teiserskas,J; Bassett,P; Oliveira,V; Mendoza,J; Slater,R; Shankaran,S (Therapeutic Hypothermia and Temperature Management, 2019)
Although therapeutic hypothermia (TH) improves outcomes after neonatal encephalopathy (NE), the safety and efficacy of preemptive opioid sedation during cooling therapy is unclear. We performed a secondary analysis of the data from a large multicountry prospective observational study (Magnetic Resonance Biomarkers in Neonatal Encephalopathy [MARBLE]) to examine the association of preemptive morphine infusion during TH on brain injury and neurodevelopmental outcomes after NE. All recruited infants had 3.0 Tesla magnetic resonance imaging and spectroscopy at 1 week, and neurodevelopmental outcome assessments at 22 months. Of 223 babies recruited to the MARBLE study, the data on sedation were available from 169 babies with moderate (n = 150) or severe NE (n = 19). Although the baseline characteristics and admission status were similar, the babies who received morphine infusion (n = 141) were more hypotensive (49% vs. 25%, p = 0.02) and had a significantly longer hospital stay (12 days vs. 9 days, p = 0.009) than those who did not (n = 28). Basal ganglia/thalamic injury (score ≥1) and cortical injury (score ≥1) was seen in 34/141 (24%) and 37/141 (26%), respectively, of the morphine group and 4/28 (14%) and 3/28 (11%) of the nonmorphine group (p > 0.05). On regression modeling adjusted for potential confounders, preemptive morphine was not associated with mean (standard deviation [SD]) thalamic N-acetylaspartate (NAA) concentration (6.9 ± 0.9 vs. 6.5 ± 1.5; p = 0.97), and median (interquartile range) lactate/NAA peak area ratios (0.16 [0.12–0.21] vs. 0.13 [0.11–0.18]; p = 0.20) at 1 week, and mean (SD) Bayley-III composite motor (92 ± 23 vs. 94 ± 10; p = 0.98), language (89 ± 22 vs. 93 ±